BOMBESIN ENHANCES TGF-β GROWTH INHIBITORY EFFECT THROUGH APOPTOSIS INDUCTION IN INTESTINAL EPITHELIAL CELLS - Liu, Xianghua (2009)
Mammalian intestinal epithelium undergoes continuous cell turn over, with cell proliferation in the crypts and apoptosis in the villus. Both transforming growth factor (TGF)-β and gastrin-releasing peptide (GRP) are involved in the regulation of intestinal epithelial cells for division, differentiation, adhesion, migration and death. Previously, we have shown that TGF-β and bombesin (BBS) synergistically induce cyclooxygenase-2 (COX-2) expression and subsequent prostaglandin E(2) (PGE2) production through p38(MAPK) in rat intestinal epithelial cell line stably transfected with GRPR (RIE/GRPR), suggesting the interaction between TGF-β signaling pathway and GRP-R. The current study examined the biological responses of RIE/GRPR cells to TGF-β and BBS. Treatment with TGF-β1 (40 pM) and BBS (100 nM) together synergistically inhibited RIE/GRPR growth and induced apoptosis. Pretreatment with SB203580 (10 µM), a specific inhibitor of p38(MAPK), partially blocked the synergistic effect of TGF-β and BBS on apoptosis. In conclusion, BBS enhanced TGF-β growth inhibitory effect through apoptosis induction, which is at least partially mediated by p38(MAPK).